(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The word retail is derived from the French word retailer, meaning to cut a piece off or to break bulk. In simple terms, it implies a first-hand transaction with the customer. Retailing can be defined as the buying and selling of goods and services. It can also be defined as the timely delivery of goods and services demanded by consumers at prices that are competitive and affordable. Retailing involves a direct interface with the customer and the coordination of business activities from end to end- right from the concept or design stage of a product or offering, to its delivery and post-delivery service to the customer. The industry has contributed to the economic growth of many countries and is undoubtedly one of the fastest changing and dynamic industries in the world today